COLLABORATIVE GOVERNANCE DALAM MEWUJUDKAN GOOD MANUFACTURING PRACTICE (GMP) PADA INDUSTRI KECIL MENENGAH (IKM): STUDI NARATIF DI KOTA DEPOK - Aldian Fadillah; Hanny Purnamasari; Nidaul Muthmainnah (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study aims to analyze the dynamics of collaborative governance in the implementation of Good Manufacturing Practice (GMP) in Small and Medium Enterprises (SMEs) in Depok City as an effort to strengthen the competitiveness of the local food industry. This study is relevant because it demonstrates the role of cross-sector collaboration in supporting food quality and safety improvements in SMEs. This study uses a qualitative approach with a narrative study design, chosen to understand the experiences of actors in depth in the collaborative process. The analysis refers to the collaborative governance framework of Ansell and Gash (2008), which includes initial conditions, institutional design, facilitative leadership, and collaborative processes. The results of the study indicate initial resource imbalances, particularly in production capacity, understanding of food safety standards, and access to technology. The facilitative leadership of the Depok City Trade and Industry Office is demonstrated through training, technical assistance, and facilitation of communication between stakeholders, which builds trust. The collaborative process is strengthened through experiential learning through visits to Terve Chocolate, which is effective because it provides hands-on learning and accelerates SMEs' understanding of GMP implementation. This study concludes that structured and participatory cross-sector collaboration is key to transforming SMEs into a more competitive food industry, and has implications for developing SME development policies in the region.